2021
DOI: 10.1111/cas.14798
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world data on microsatellite instability status in various unresectable or metastatic solid tumors

Abstract: Microsatellite instability‐high (MSI‐H) is an important biomarker for predicting the effect of immune checkpoint inhibitors (ICIs) on advanced solid tumors. Microsatellite instability‐high is detected in various cancers, but its frequency varies by cancer type and stage. Therefore, precise frequency is required to plan ICI therapy. In this study, the results of MSI tests actually carried out in clinical practice were investigated. In total, 26 469 samples of various cancers were examined between December 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 23 publications
2
63
0
Order By: Relevance
“…Figure 2 shows the frequency of MSI‐H by primary site in Japanese patients with various unresectable or metastatic solid tumors. The frequency of endometrial cancer was the highest at 17%, followed by small intestine, gastric, duodenal, and colon cancer, and the rate of ovarian cancer was 2.2% 47 . This frequency is almost the same as in Europe and the United States 44 .…”
Section: Lynch Syndrome (Ls)mentioning
confidence: 70%
See 1 more Smart Citation
“…Figure 2 shows the frequency of MSI‐H by primary site in Japanese patients with various unresectable or metastatic solid tumors. The frequency of endometrial cancer was the highest at 17%, followed by small intestine, gastric, duodenal, and colon cancer, and the rate of ovarian cancer was 2.2% 47 . This frequency is almost the same as in Europe and the United States 44 .…”
Section: Lynch Syndrome (Ls)mentioning
confidence: 70%
“…Akagi et al reported that the overall frequency of MSI‐H was 3.72% in the results of 26 237 MSI tests in Japanese patients with various unresectable or metastatic solid tumors 47 . Figure 2 shows the frequency of MSI‐H by primary site in Japanese patients with various unresectable or metastatic solid tumors.…”
Section: Lynch Syndrome (Ls)mentioning
confidence: 99%
“…Only a few biliary tract cancer patients were included in these studies, owing to the rarity of these alterations. MSI-high biliary tract cancer was reported in 2.22% and 1.50% of Japanese cholangiocarcinoma and gallbladder cancer patients, respectively [ 71 ]. NTRK fusion positivity was reported in only 0.18% of biliary tract cancers [ 72 ].…”
Section: Second-line Chemotherapy For Advanced Biliary Tract Cancermentioning
confidence: 99%
“…Among them, MSI-H has been an established biomarker for ICIs across tumor types. The prevalence of MSI-H was found to be~5% in Japanese patients with metastatic or recurrent GC [5]. The clinicopathologic profile of MSI-H tumors includes a local and systemic antitumoral immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Not amenable to curative approaches such as definitive chemoradiation or surgery (5). No prior systemic anticancer treatment given as primary therapy for advanced or metastatic disease.…”
mentioning
confidence: 99%